Teenage pregnancy characterization from a medical office. Cienfuegos 2009 – 2023 - Mileidy Portal Amador; Alina Esther González Hermida; María Eugenia Monjes Pérez; Beatriz Santos González (Medisur)
Foundation: several authors have showed an increase in adolescent age fertility. Teenage pregnancy is a health problem and a worldwide concern. In Cuba the medical offices network has a fundamental function in its work in the community. Objective: to characterize pregnancy in adolescents from a family doctor's office. Methods: a descriptive study was carried out in a family doctor's 11 of health area V, in Cienfuegos, from 2009 to 2023. Pregnant adolescents selected during that time were included (n= 15). The studied variables were: age, continuity of studies, relationship, age of sexual relations start, family functioning (using family functionality scale), use of contraception and main obstetric conditions. Results: pregnant adolescents aged 17 to 19 years (86%) predominated. 73% quit school, and 80% had a stable partner at the time of conception. 47% began sexual relations between 17 and 19 years of age; 60% came from dysfunctional families; while 73% did not use any contraceptive method. Anemia was the main obstetric condition (86%). Conclusions: school quit and dysfunctional families stood out in the analyzed series as determining factors, occurring in high proportions.